Religião e comida: como as práticas alimentares no contexto religioso auxiliam na construção do homem - Souza, Patricia Rodrigues de (2014)
The present study explores food practices of different natures in several religious contexts in a comparative manner. The main goal is to drive attention to the fact that all religions, if they do not have a pre established food conduct by their doctrines, they have a say about food and how it affects religious disposition. This research is based on exclusive bibliographical data taken from religious doctrines, as well as texts produced by believers and also few analysis done by food specialists, anthropologists and sociologists of food and food practices. Man, its food and its religion are studied under the evolutionistic perspective. We have tried to retrieve the origins of the relationship between food, food practices and religion. We have observed the construction of this relation in detail in order to detect general functions among the religions studied here. We have concluded food has common functions at several levels in different religions, which constitutes a significant point to compare. The effects of food practices touch individuals in physical and psychological aspects, once it determines the amount and quality of what is to be eaten. It also has cultural effects, since cultural values are attributed to foods and later, these values are either absorbed or rejected according to cultural rules that are similar to rules of language. In the same way, there are social effects, since food in religious case can be a frontier and an identity element to the groups; in terms of social effects, the agreement about the same food and food practices favors the cohesion of the group and excludes those of different practices. For all these aspects food and food practices constitute a resource that helps religion to represent and reinforce its values